Improving Elementary School Students' Learning Outcomes in Science Learning by Using the Talking Stick Type Cooperative Model Assisted by Mystery Box Media - Tisa Maghfirah; Syahidan Nurdin (Indonesian Journal of Education and Social Humanities, 2025)
This research is motivated by the low learning outcomes of students in the Natural and Social Sciences learning in class IV MIN 21 Aceh Besar due to the lack of active student involvement in the learning process. The low interaction, participation, and response of students have an impact on less than optimal understanding of concepts. This study aims to: (1) describe teacher activities in implementing the Talking Stick type cooperative learning model assisted by Mystery Box media; (2) describe student activities during learning; and (3) determine the improvement in student learning outcomes after the implementation of the model. The method used is Classroom Action Research which is carried out in two cycles, each including the planning, implementation, observation, and reflection stages. Data were collected through observations of teacher and student activities as well as learning outcome tests. Data analysis was carried out using a percentage formula. The results of the study showed a significant increase, namely teacher activity increased from 71.15% to 92.30%, student activity from 69.23% to 88.46%, and student learning outcome completion from 57.14% in cycle I to 90.47% in cycle II. Thus, the Talking Stick type cooperative learning model assisted by Mystery Box media has proven effective in increasing student activity and learning outcomes in the science subject.